Programme level implementation of malaria rapid diagnostic tests (RDTs) use: outcomes and cost of training health workers at lower level health care facilities in Uganda - Kyabayinze, Daniel J.; Nakanjako, Damalie; Tibenderana, James K.; Geetruyden, Jean Pierre Van (BMC Public Health, 2012)
The training of health workers in the use of malaria rapid diagnostic tests (RDTs) is an important component of a wider strategy to improve parasite-based malaria diagnosis at lower level health care facilities (LLHFs) where microscopy is not readily available for all patients with suspected malaria. This study describes the process and cost of training to attain competence of lower level health workers to perform malaria RDTs in a public health system setting in eastern Uganda. Health workers from 21 health facilities in Uganda were given a one-day central training on the use of RDTs in malaria case management, including practical skills on how to perform read and interpret the test results. Successful trainees subsequently integrated the use of RDTs into their routine care for febrile patients at their LLHFs and transferred their acquired skills to colleagues (cascade training model). A cross-sectional evaluation of the health workers’ competence in performing RDTs was conducted six weeks following the training, incorporating observation, in-depth interviews with health workers and the review of health facility records relating to tests offered and antimalarial drug (AMD) prescriptions pre and post training. The direct costs relating to the training processes were also documented. Overall, 135 health workers were trained including 63 (47%) nursing assistants, a group of care providers without formal medical training. All trainees passed the post-training concordance test with ≥ 80% except 12 that required re-training. Six weeks after the one-day training, 51/64 (80%) of the health workers accurately performed the critical steps in performing the RDT. The performance was similar among the 10 (16%) participants who were peer-trained by their trained colleagues. Only 9 (14%) did not draw the appropriate amount of blood using pipette. The average cost of the one-day training was US$ 101 (range $92-$112), with the main cost drivers being trainee travel and per-diems. Health workers offered RDTs to 76% of febrile patients and AMD prescriptions reduced by 37% six weeks post-training. One-day training on the use of RDTs successfully provided adequate skill and competency among health workers to perform RDTs in fever case management at LLHF in a Uganda setting. The cost averaged at US$101 per health worker trained, with the main cost drivers being trainee travel and per diems. Given the good peer training noted in this study, there is need to explore the cost-effectiveness of a cascade training model for large scale implementation of RDTs.